1999
DOI: 10.1016/s0022-5347(05)68071-8
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Sparing Surgery for Localized Renal Cell Carcinoma: Impact of Tumor Size on Patient Survival, Tumor Recurrence and TNM Staging

Abstract: Following nephron sparing surgery for localized sporadic renal cell carcinoma cancer-free survival is significantly better in patients with tumors 4 cm. or less compared to those with larger tumors. The usefulness of the current TNM staging system can be improved by subdividing T1 tumors into T1a (4 cm. or less) and T1b (4 to 7 cm.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
212
1
38

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(260 citation statements)
references
References 6 publications
9
212
1
38
Order By: Relevance
“…42,[76][77][78][79][80] These findings are not surprising as detailed analysis of tumor size as a continuous variable has shown that the probability of death increases with tumor size (3.51 Â for each doubling of tumor size). 81 As a consequence any arbitrary cut point will likely be significantly associated with survival providing that the sample size is sufficiently large.…”
Section: Tumor Size (Tnm Categories T1 and T2)mentioning
confidence: 99%
“…42,[76][77][78][79][80] These findings are not surprising as detailed analysis of tumor size as a continuous variable has shown that the probability of death increases with tumor size (3.51 Â for each doubling of tumor size). 81 As a consequence any arbitrary cut point will likely be significantly associated with survival providing that the sample size is sufficiently large.…”
Section: Tumor Size (Tnm Categories T1 and T2)mentioning
confidence: 99%
“…We collapsed tumor size into 2 clinically relevant groups based on a 4-cm threshold. 14 We assigned median Census-tract income and Censustract percentage of nonhigh school graduates as patient-level measures of income and education, respectively. 25 We measured pre-existing comorbidity by using a modification of the Charlson Index 26 to identify comorbid conditions (including diabetes, renal insufficiency, and cardiovascular disease) from inpatient and physician claims that were submitted during the 12 months before the index admission for kidney cancer surgery.…”
Section: Patient-level Covariatesmentioning
confidence: 99%
“…1,2,4,11,12 In synchronicity with the gradual dissemination of laparoscopic radical nephrectomy, 2,4 multiple investigators reported that, for selected patients with smaller renal tumors, partial nephrectomy yields oncologic outcomes that are indistinguishable from the outcomes achieved by radical excision. [13][14][15] Partial nephrectomy also preserves long-term renal function 16,17 while reducing over-treatment of patients with benign 18 or clinically indolent 19 tumors.…”
mentioning
confidence: 99%
“…This information suggests that tumor growth significantly influences the prognosis of this lethal disease. The majority of studies that have reported a large number of patients indicate that the stratification size related to RCC prognosis is between 4 and 5 cm (3,4).…”
Section: Clinical Urolog� Clinical Urolog� Doi: 101590/s1677-5538201mentioning
confidence: 99%